Simulating blood pressure and end tidal CO2 in a CPR training manikin. (October 2019) - Widmann, Nicholas; Sutton, Robert; Buchanan, Newton; Niles, Dana E.; Nazareth, Godfrey; Nadkarni, Vinay; Maltese, Matthew R.
Highlights: CPR training manikin simulates blood pressure and end tidal CO2 from mechanics of CPR. Simulated bed-side monitor displays real-time waveforms realistic in shape and value. 34 trained clinicians validated manikin as accurate and helpful for CPR training. Abstract: Background and Objective: The American Heart Association supports titrating the mechanics of cardiopulmonary resuscitation (CPR) to blood pressure and end tidal carbon dioxide (ETCO2) thresholds during in-hospital cardiac arrest. However, current CPR manikin training systems do not prepare clinicians to use these metrics to gauge their performance, and currently provide only feedback on hand placement, depth, rate, release, and interruptions of chest compressions. We addressed this training hardware deficiency through development of a novel CPR training manikin that displays simulated blood pressure and ETCO2 waveforms in real time on a simulated clinical monitor visible to the learner, reflecting the mechanics of chest compressions provided to the manikin. Such a manikin could improve clinicians' CPR technique while also training them to titrate CPR quality to physiologic blood pressure and ETCO2 targets as performance indicators. Methods: We used data and key findings from 4 human and 6 animal studies (including 132 human subjects, 61 pigs, and 16 dogs in total) to develop an algorithm that simulates blood pressure and ETCO2 waveforms based on compression mechanics for a pediatric patient. We modified an off-the-shelf infant manikin to incorporate a microcontroller sufficient to process the aforementioned algorithm, and a tablet computer to wirelessly display the simulated waveform. We recruited clinicians with in-hospital CPR experience to perform compressions with the manikin and complete a post-test survey on their satisfaction with designated elements of the manikin and display. Results: 34 clinicians performed CPR on the prototype manikin system that simulates real-time bedside monitoring of blood pressure and ETCO2. 100% of clinicians surveyed reported "satisfaction" with the blood pressure waveform. 97% said they thought depth was accurately reflected in blood pressure (0% inaccurate, 3% not sure). 88% reported an accurate chest compression rate modification effect on blood pressure and ETCO2 (3% inaccurate, 9% not sure) and 59% an accurate effect of leaning (6% inaccurate, 35% not sure). Most importantly, all 34 respondents responded "yes" when asked if they thought this system would be helpful for CPR training. Conclusion: A CPR manikin that simulates blood pressure and ETCO2 was successfully developed with acceptable relevance, performance and feasibility as a CPR quality training tool.